Visual Elements of Semar Calligraphy on Cirebon Glass Painting of Kusdono’s Work - Yayah Rukiah; Sarwanto Sarwanto; Sutarno Sutarno; Sunardi Sunardi (Pascasarjana Institut Seni Indonesia Surakarta, 2020)
This research is focused on visual elements contained in Kusdono's Cirebon glass painting. To examine the meaning of visual elements, the writer uses the aesthetic approach and Erwin Panofsky's iconographic approach through 3 stages: the description of pro-iconography, iconography, and finally, iconology. The methodology used is a descriptive qualitative research method, with data collection techniques from books and journals related to the research object. The purpose of this study is to examine and uncover the meaning of Cirebon glass paintings. These research results are Semar as the principal figure in the clown who always do good, keep the truth, and obey His teachings closely related to Islam. Arabic calligraphy reinforces Semar's figure. Many use mega cloudy and wadasan ornaments in the Cirebon glass painting, which are Cirebon batik motifs. Also, the colors used are coastal colors due to the City of Cirebon's geographical location close to the beach.